WeHome: Smart Home Automation Control System using IoT and Android Mobile Application - Mahadhir Alam Shah, Siti Nur Afifah (IRC, 2020)
This paper work is mainly focused on Internet of Things (IoT) based on home automation using Raspberry Pi. IoT technology helps to control basic home appliances automatically through internet by using mobile devices or smartphones. Up to this new era, smart home automation system can help in having a centralized method to control all home appliances. This system will control home appliances through Android apps based on Raspberry Pi. The mobile application consists with GUI that have login system which allow user to insert their username and password which will ensure that it cannot be easily hacked. Other than that, the mobile application also will show the home appliances details (e.g ON/OFF conditions) for user view. The system will be benefit on saver energy consumed by home appliances.